Structural alterations and liver function in acute cholangitis - Torterolo, Edgardo; Olazábal, Mario; Beltrán, Ricardo; Czarnevicz, Daniel; Ferreira, Ciro; Silva, Celso (Cirugía del Uruguay, 1994)
With the purpose of evaluating the relationship between the clinical severity of acute cholangitis and the anatomic liver alterations, it was decided to put to the test a method of assessing the degree of severity of these patients and investigate the pathogenic and prognostic role of the histologic /esions and hepatic dysfunction. The hepatic histopathologic alterations were classified according to degrees of increasing severity in conjuncion with the parenchymal damage secondary to biliary obstruction.